Butylated Hydroxyanisole-Induced Alterations in the Stomach and Kidney of Albino Rat : A Mini Review - Makarwar, Yamini; Dhurvey , Varsha (International Journal of Scientific Research in Biological Sciences, 2025)
Butylated hydroxyanisole or commonly abbreviated as BHA, is mostly employed as a food preservative to prolong the products shelf life by stopping or postponing oxidation processes. The commercial product is usually a combination of 90% 3-BHA and 10% 2-BHA. BHA is generally considered safe when used as a food additive, Since, butylated hydroxyanisole is so widely used, it can be detected in both human tissues and a variety of environmental matrices. Humans are mostly exposed to butylated hydroxyanisole through their diet. One of the primary metabolites that butylated hydroxyanisole can produce under different conditions is tert-butyl hydroquinone (TBHQ). According to a number of studies, butylated hydroxyanisole may harm the thyroid system and result in growth and metabolic problems, neurotoxicity, and cancer. One of the main priorities is to minimize the harmful effects of BHA. Future studies should concentrate on identifying safe, non-toxic, and eco-friendly substitutes for BHA. This review aims to highlight the hazardous and detrimental effects of butylated hydroxyanisole in animal models. We are confident that this assessment will yield important data about the toxicological nature of butylated hydroxyanisole, that will aid in the development of safe usage guidelines.